Higher Incidence of Stroke in Severe COVID-19 Is Not Associated With a Higher Burden of Arrhythmias: Comparison With Other Types of Severe Pneumonia - Jirak, Peter; Shomanova, Zornitsa; Larbig, Robert; Dankl, Daniel; Frank, Nino; Seelmaier, Clemens; Butkiene, Dominyka; Lichtenauer, Michael; Mirna, Moritz; Strohmer, Bernhard; Sackarnd, Jan; Hoppe, Uta C.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Thromboembolic events, including stroke, are typical complications of COVID-19. Whether arrhythmias, frequently described in severe COVID-19, are disease-specific and thus promote strokes is unclear. We investigated the occurrence of arrhythmias, and stroke during rhythm monitoring in critically ill COVID-19, compared to severe pneumonias of other origin. Methods and Results: Recruited were 120 critically ill patients requiring mechanical ventilation in three European tertiary hospitals, including n=60 COVID‐19, matched according to risk factors for occurrence of arrhythmias to n=60 patients from a retrospective consecutive cohort of severe pneumonias of other origin. Arrhythmias, mainly atrial fibrillation (AF), were frequent in COVID-19. However, when compared to nonCOVID-19, no difference was observed with respect to ventricular tachycardias (VT) and relevant bradyarrhythmias (VT 10.0 vs. 8.4 %, p=ns and asystole 5.0 vs. 3.3%, p=ns) with consequent similar rates of cardiopulmonary resuscitation (6.7 vs. 10.0% p=ns). AF was even more common in nonCOVID-19 (AF 18.3 vs. 43.3%, p=0.003; newly onset AF 10.0 vs. 30.0%, p=0.006) which resulted in higher need for electrical cardioversion (6.7 vs. 20.0%, p=0.029). Despite these findings and comparable rates of therapeutic anticoagulation (TAC), the incidence of stroke was higher in COVID-19 (6.7.% vs. 0.0, p=0.042). These events happened also in absence of AF (50%) and with TAC (50%). Conclusions: Arrhythmias were common in severe COVID-19, consisting mainly of AF, yet less frequent than in matched pneumonias of other origin. A contrasting higher incidence of stroke independent of arrhythmias observed also with TAC, seems to be an arrhythmia-unrelated disease-specific feature of COVID-19.